Chemical Kinetic Modeling of Soot Precursors Formation Characteristics in Ethylene Oxidation - Zhang, Yindi; Ruan, Longfei; Li, Yong (Asian Journal of Chemistry, 2014)
The chemical kinetics modeling study of soot precursor characteristics in laminar premixed ethylene flame at different pressure and broad ranged of equivalence ratio (stoichiometric and rich flames) was conducted using CHEMKIN-PRO and advanced functions. In the kinetic modeling work, the formation of soot precursors for ethylene flame is investigated by using Marinov and Dagaut gas mechanisms, respectively. The prediction focused on temperature, small molecules, single-ring aromatics benzene and polycyclic aromatic hydrocarbons macromolecules intermediates using one-dimensional laminar premix flame (PREMIX) model. By comparison with the experimental data, the results show that the distributions of flame temperature and the mole fractions for small molecules (following C6H6) are in good agreement experimental data for Marinov mechanism. However, the prediction for C6H6 and macromolecule polycyclic aromatic hydrocarbon intermediates, there have no obvious merits between two mechanisms.